2021
DOI: 10.3390/e23050500
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Alterations in the Distribution of Neural Network Weights in Dementia Due to Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder which has become an outstanding social problem. The main objective of this study was to evaluate the alterations that dementia due to AD elicits in the distribution of functional network weights. Functional connectivity networks were obtained using the orthogonalized Amplitude Envelope Correlation (AEC), computed from source-reconstructed resting-state eletroencephalographic (EEG) data in a population formed by 45 cognitive healthy elderly controls, 69 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Whereas a disordered network with both reduced, and increased connectivity are associated with dysconnectivity or dysconnection. Functional connectivity studies in AD have shown a reduction in connectivity strength in cortical regions especially between distant electrodes in inter and intra‐hemispheres (Afshari & Jalili, 2017; Babiloni et al, 2016; Das & Puthankattil, 2020; Gurja et al, 2021; Jeong et al, 2001; Mammone et al, 2017; Musaeus et al, 2019; Pijnenburg et al, 2004; Revilla‐Vallejo et al, 2021; Sankari et al, 2011; Smailovic et al, 2020; Yan et al, 2021). Reduction in information transfer in AD patients across distant electrodes in the right hemisphere and between hemispheres was observed even without frequency band based analysis (Jeong et al, 2001).…”
Section: Eegdata For Connectivity Analysismentioning
confidence: 99%
“…Whereas a disordered network with both reduced, and increased connectivity are associated with dysconnectivity or dysconnection. Functional connectivity studies in AD have shown a reduction in connectivity strength in cortical regions especially between distant electrodes in inter and intra‐hemispheres (Afshari & Jalili, 2017; Babiloni et al, 2016; Das & Puthankattil, 2020; Gurja et al, 2021; Jeong et al, 2001; Mammone et al, 2017; Musaeus et al, 2019; Pijnenburg et al, 2004; Revilla‐Vallejo et al, 2021; Sankari et al, 2011; Smailovic et al, 2020; Yan et al, 2021). Reduction in information transfer in AD patients across distant electrodes in the right hemisphere and between hemispheres was observed even without frequency band based analysis (Jeong et al, 2001).…”
Section: Eegdata For Connectivity Analysismentioning
confidence: 99%
“…Due to the complexity of the problem, multidisciplinarity is clear in most of these works. This is the case of the study carried out by Revilla-Vallejo and colleagues [ 7 ]. They propose a new methodology based on analyzing the distribution of the weights of the brain network from EEG after source reconstruction to improve understanding of the neural mechanisms associated with the progression of Alzheimer disease (AD).…”
mentioning
confidence: 99%